Distribusi Kebutuhan Air Bersih Untuk Pasien COVID-19 Melalui Simulasi Epanet di RSUD Genteng Banyuwangi - Wahyudin, Iqbal; Erwanto, Zulis (Indonesian Society of Applied Science, 2024)
Regional general hospital of genteng is a public health service, due to the increase in Covid-19 patients in 2020, the function of Class 1 and Isolation Building was carried out. The capacity of the two buildings is 92 people, it is necessary to ensure that water distribution is met. This study aims to simulate the distribution of clean water in Class 1 and Isolation Building of Genteng Hospital using Epanet 2.0. Determination of the number of users of Class 1 and Isolation Building using Least Square and Geometric projection methods for 9 months. Then a water distribution simulation was carried out using the Epanet 2.0 program. Simulation of 100% service water distribution resulted in a discharge requirement of 0.347 l/s in Class 1 Building with 3/4“ pipe diameter, with an average velocity of 0.55 m/s, an average headloss unit of 32.52 m/km. Simulation of water distribution for the 100% service isolation building requires a discharge of 0.406 l/s with an average velocity of 0.50 m/s, an average headloss unit of 24.84 m/km. Adding 90 users, then the service becomes 125% adding 1 bathroom unit on the 2nd floor, it takes a water discharge of 0.623 l/s, with an average velocity of 0.73 m/s, an average headloss unit of 51.02 m/km.